The redox status of salinity-stressed Chenopodium quinoa under salicylic acid and sodium nitroprusside treatments - Hajihashemi, Shokoofeh; Jahantigh, Omolbanin; Alboghobeish, Sahira (Frontiers in Plant Science, 2022)
Abstract Spreading the cultivation of crops with high nutritional values such as Quinoa demands a wide area of research to overcome the adverse effects of environmental stress. The present study aimed at investigating the role of salicylic acid (SA) and sodium nitroprusside (SNP), as an NO donor, priming at improving the antioxidant defense systems in boosting salinity tolerance in Chenopodium quinoa. These two treatments individually, SA (0.1 mM) or SNP (0.2 mM) or their combination, significantly improved the function of both enzymatic and non-enzymatic antioxidants. The SA and SNP priming significantly reduced superoxide dismutase activity, which was accompanied by a significant decrease in the H2O2 accumulation under salinity stress (100 mM NaCl). The SA and SNP treatment increased the activity of enzymatic antioxidants (e.g., catalase, ascorbate peroxidase, peroxidase and glutathione reductase) and accumulation of non-enzymatic antioxidants (e.g. ascorbate-glutathione pools, α-tocopherol, phenols, flavonoids, anthocyanins and carotenoids) to suppress the oxidative stress-induced by salinity stress. Under SA and SNP treatment, the upregulation of antioxidant mechanisms induced a significant increase in chlorophyll florescence, chlorophylls, carotenoids and proteins, as well as, a significant reduction in malondialdehyde content in the salinity-stressed plants. Besides, the foliar application of SA or/and SNP led to a significant increase in accumulation of osmoprotectant molecules of sugars and proline to overcome osmotic stress-induced by salinity stress. In conclusion, SA and SNP priming can effectively combat salinity stress through improving the redox status of plants.